2017
DOI: 10.20473/jbe.v5i22017.185-194
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Socioeconomic and Nutritional with Risk of Tuberculosis in DM Type 2 Patient

Abstract: ABSTRAKDiabetes mellitus (DM) adalah penyakit yang disebabkan penggunaan insulin yang kurang efektif. Jawa Timur merupakan provinsi yang masuk 10 besar prevalensi Diabetes se-Indonesia. Pasien DM berisiko lebih tinggi terkena TB. Tujuan penelitian ini untuk mengetahui hubungan sosioekonomi dan status gizi dengan risiko terjadinya TB pada penderita DM tipe 2 di Kecamatan Tambaksari. Penelitian ini merupakan penelitian kuantitatif retrospektif dengan desain case control penyepadanan umur dan jenis kelamin. Sampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In line with this study based on the results of bivariate analysis that work is associated with the incidence of active pulmonary TB in people with type 2 DM (p = 0.02). The results of research by Hapsari and Isfandiari, (2017) on DM patients seeking treatment at all health centers in the Tambaksari District area in 2016 showed similar results, where there was a significant relationship between employment status and the incidence of pulmonary TB [28]. Different things were found in a study by Yosephine et al, (2021) on factors influencing the incidence of pulmonary TB in patients with DM that there was no significant relationship between employment status and the incidence of active pulmonary TB in people with DM (OR=0.802; 95%CI: 0.377-1.703) [29].…”
Section: Active Pulmonary Tb P-value Pr (95%ci) Yesmentioning
confidence: 74%
See 1 more Smart Citation
“…In line with this study based on the results of bivariate analysis that work is associated with the incidence of active pulmonary TB in people with type 2 DM (p = 0.02). The results of research by Hapsari and Isfandiari, (2017) on DM patients seeking treatment at all health centers in the Tambaksari District area in 2016 showed similar results, where there was a significant relationship between employment status and the incidence of pulmonary TB [28]. Different things were found in a study by Yosephine et al, (2021) on factors influencing the incidence of pulmonary TB in patients with DM that there was no significant relationship between employment status and the incidence of active pulmonary TB in people with DM (OR=0.802; 95%CI: 0.377-1.703) [29].…”
Section: Active Pulmonary Tb P-value Pr (95%ci) Yesmentioning
confidence: 74%
“…Malaise occurs due to the process of hypercatabolism due to increased proinflammatory cytokines caused by TB infection, increased proinflammatory cytokines also cause metabolic dysregulation, especially in people with type 2 DM [28]. This statement is supported by research conducted by Tong et al, (2021) out of 312 TB-DM subjects, 182 people or 58.3% had complaints of malaise (p = 0.001).…”
Section: Active Pulmonary Tb P-value Pr (95%ci) Yesmentioning
confidence: 81%
“…The decline in the immune system can be influenced by various factors, including socioeconomic and nutritional status. Malnutrition is a state of abnormal nutritional status in the body caused by metabolic disorders or body balance, a deficiency of nutritional intake, or an excess of nutritional intake (Hapsari & Isfandiari, 2017). Decreased immune conditions also cause TB germs to be active, resulting in the activation of various inflammatory mediators such as TNF-Alfa, which causes a decrease in appetite, and Interleukin-1, which can increase the basal metabolic rate, and then these two things cause weight loss so that the BMI measurement becomes normal (Restrepo, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…The crude prevalence rate slightly higher in males compared to females [6]. Research by Hapsari and Muhammad [7] in Tambaksari Subdistrict Surabaya showed that TB patients with DM are most likely found in males, as many as 23 people (60.5%). This is under WHO report [8] that more men suffered from TB globally.…”
Section: A Characteristics Of Tb-dm Patientsmentioning
confidence: 91%